2006
DOI: 10.1111/j.1574-6968.2006.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping ofOchrobactrum anthropibyrecA-based comparative sequence, PCR-RFLP, and 16S rRNA gene analysis

Abstract: A recA-PCR restriction fragment length polymorphism assay was developed to study intraspecies variation among Ochrobactrum anthropi. Primers deduced from the known recA gene sequence of the genetically closely related genus Brucella allowed the specific amplification of a 1065 bp recA fragment from each of the 38 O. anthropi and the eight Brucella strains investigated. RecA was also amplified from the type strains of O. intermedium, O. tritici, and O. lupini but could not be generated from O. grignonense and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 25 publications
3
61
1
Order By: Relevance
“…Both copies of the omp2 gene were shown to contain motifs typical of marine mammal isolates. 16S rRNA gene sequence data, as well as recA gene sequences, identify the strains from marine mammals as belonging to the genus Brucella (Scholz et al, 2006).…”
mentioning
confidence: 99%
“…Both copies of the omp2 gene were shown to contain motifs typical of marine mammal isolates. 16S rRNA gene sequence data, as well as recA gene sequences, identify the strains from marine mammals as belonging to the genus Brucella (Scholz et al, 2006).…”
mentioning
confidence: 99%
“…The 16S rRNA gene-based tree shown in Fig. 1 results from a neighbour-joining reconstruction using the Kimura two-parameter correction and 1000 resamplings for bootstrap analysis.The partial recA sequence of strain KSS 7.8 T was analysed as described previously (Scholz et al, 2006). The PCR was performed with primers RecA-PsOchro-f (59-AAGGCTC-TGGACGCGGCACT-39) and RecA-PsOchro-r (59-CGC-AAGGTCAGTTC AATCTCAT-39).…”
mentioning
confidence: 99%
“…The partial recA sequence of strain KSS 7.8 T was analysed as described previously (Scholz et al, 2006). The PCR was performed with primers RecA-PsOchro-f (59-AAGGCTC-TGGACGCGGCACT-39) and RecA-PsOchro-r (59-CGC-AAGGTCAGTTC AATCTCAT-39).…”
mentioning
confidence: 99%
“…at the inter-and intraspecies level (Scholz et al, 2006) confirmed isolate RMA 16449 as O. intermedium (results not shown).…”
Section: Jmm Correspondencementioning
confidence: 69%
“…Hence isolate RMA 16994 appeared to be more closely related to O. intermedium than to O. anthropi. Identification of isolate RMA 16994 as O. intermedium was confirmed by the presence of the O. intermedium-specific sequence motifs ggctaat and ggttagtggagacactatcc at positions nt 487-493 and nt 905-924 of the 1390 bp 16S rRNA gene fragment as described by Scholz et al (2006). The second motif is also shared with Brucella spp.…”
Section: Jmm Correspondencementioning
confidence: 83%